Propionibacterium acnes-Derived Circulating Immune Complexes in Sarcoidosis Patients - Keisuke Uchida; Asuka Furukawa; Akiko Yoneyama; Haruhiko Furusawa; Daisuke Kobayashi; Takashi Ito; Kurara Yamamoto; Masaki Sekine; Keiko Miura; Takumi Akashi; Yoshinobu Eishi; Kenichi Ohashi (Microorganisms, 2021)
Propionibacterium acnes is a potential etiologic agent of sarcoidosis and a dysregulated immune response to the commensal bacterium is suspected to cause granuloma formation. P. acnes-derived insoluble immune complexes were recently demonstrated in sinus macrophages of sarcoidosis lymph nodes, suggesting local proliferation of the bacterium in affected organs. In the present study, we developed a method for detecting P. acnes-derived immune complexes in human blood by measuring the concentration of P. acnes-specific lipoteichoic acid (PLTA) detectable after an antigen retrieval pretreatment of plasma samples. Before pretreatment, anti-PLTA antibody was detected and PLTA could not be detected, in all plasma samples from 51 sarcoidosis patients and 35 healthy volunteers. After pretreatment, however, a significant level of PLTA (>105 ng/mL) was detected in 33 (65%) sarcoidosis patients and 5 (14%) control subjects, with 86% specificity and 65% sensitivity for sarcoidosis. In both groups, plasma anti-PLTA antibody titers did not differ between samples with and without detection of PLTA. PLTA levels were abnormally increased (>202 ng/mL) in 21 (41%) sarcoidosis patients. These findings suggest that P. acnes-derived circulating immune complexes present in human blood are abnormally increased in many sarcoidosis patients, presumably due to local proliferation of the bacterium in the affected organs.